KNOWLEDGE, ATTITUDE AND PRACTICE REGARDING OBESITY AMONG PATIENTS, AT AGA KHAN UNIVERSITY HOSPITAL, KARACHI - Qidwai, Waris; Azam, Syed Iqbal (Journal of Ayub Medical College Abbottabad, 2004)
Background: Obesity is a major public health problem and responsible for significant morbidity and mortality among our patients. It is important to study the knowledge, attitude and practices with regard to obesity among patients, in order to devise interventional strategies. Methods: Patients visiting the out-patient clinics of Aga Khan University Hospital, Karachi, were included in the study. The interview was questionnaire-based and recorded the demographic profile of the patients and questions relevant to the objective of the study. The ethical requirements for the study were met. SPSS computer software was used for data management. A hundred patients were surveyed. Results: Women (55%) were more than men (45%), under 39 years (73%), married (55%), with graduate or more education ( 65%), in private service (44%) and housewives (19%). A substantial number of respondents (75%) understood the meaning of obesity and considered it a major health problem (90%). More respondents felt the need to reduce weight (52%), despite the fact that lesser number considered themselves to be overweight or obese (34%). A majority of the respondents did exercise (59%) but a minority did it more than five times a week (17%) and more than 30 minutes on each occasion (31%). A substantial proportion of the respondents stated their preference for oily food (34%), sweets (34%), fried food (40%), red meat (21%), fast food (37%), butter, cheese and cream (31%). Conclusions: We have found a significant level of understanding about obesity among our patients. Physical exercise and dietary measures to control body weight are lacking despite the desire to have appropriate body weight. There is a need and we strongly recommend patient education programs to control obesity. Keywords: Obesity, Bodyweight, Physical exercise, Diet